Subset simulation-based reliability analysis of the corroding natural gas pipeline - Yu, Weichao; Huang, Weihe; Wen, Kai; Zhang, Jie; Liu, Hongfei; Wang, Kun; Gong, Jing; Qu, Chunxu (Reliability engineering & system safety, 2021)
•Subset simulation is applied to evaluate the reliability of corroding pipeline.•The competitiveness of failure modes and correlation of defects are considered.•A numerical example is proposed to illustrate the feasibility of the methodology.•The effect of the correlation of defects on system reliability is investigated. In this study, a subset simulation-based methodology is developed to evaluate the time-dependent reliability of the corroding pipeline with multiple correlated corrosion defects. Two competing failure modes, namely small leak and burst, are considered in the methodology. Firstly, the time-dependent structural reliability model of the two competing failure modes is established. Then, the computational framework for implementing subset simulation for failure probability estimation of the individual corrosion defect is presented. Thereafter, a procedure to calculate the system reliability of the entire pipeline with correlated corrosion defects is proposed. Moreover, a numerical example based on a real natural gas pipeline is proposed, and the time-dependent failure probabilities of both the small leak and burst are predicted, which are compared with the evaluation results produced by the direct Monte Carlo simulation and Kriging method. By means of numerical example, the accuracy and efficiency of our methodology are demonstrated. Furthermore, a sensitivity analysis is performed to investigated the effect of the correlation of the corrosion defects on the system reliability, and the results indicate that the correlation exert great impact on system reliability.